Mengenal Sejarah Kerajaan Islam Untuk Pembentukan Karakter Siswa di Sekolah Dasar - Hesti Hopipah Aliyani; Nuraeni Pebriani, Yulia; Deti Rostika; Ranu Sudarmansyah (Jurnal Multidisiplin Indonesia, 2023)
This article discusses the importance of including the history of the Islamic kingdom into the elementary school curriculum as an effort to shape students' character. The history of the Islamic kingdom has a central role in shaping identity and positive values ​​in the younger generation. By deepening students' understanding of the heyday of the Islamic kingdom, they can develop a sense of pride in their cultural heritage, which becomes a strong basis for forming characters with high traditional values. In addition, this article highlights ethical and moral values ​​that can be drawn from the history of Islamic empires, such as justice and tolerance, to inspire students to develop responsible character. This approach also opens up opportunities to integrate the values ​​of diversity in the curriculum, enriching students' understanding of tolerance and teaching them to appreciate differences. Thus, including the history of the Islamic kingdom in the elementary school curriculum not only helps build a strong cultural foundation, but also shapes students' characters who have integrity, responsibility, and have a deep understanding of Islamic history and values.